Prinsip Kerja Sama dalam Rapat Sidi-Sidi Jemaat Maranatha Waijoi-Jikomoi (Kajian Pragmatik Implikatur Percakapan) - Boriri, Agus; Poroco, Novita (Titian: Jurnal Ilmu Humaniora, 2024)
This research aims to determine the application of the principle of cooperation in the Sidi-Sidi meeting of the Maranatha Waijoi-Jikomoi Congregation. This research was conducted at the Maranatha congregation in Waijoi village. The data collection techniques for this research are observation and documentation in a qualitative approach. In identifying research data, researchers use data reduction, data presentation and drawing conclusions. The results found in this research are that the principle of cooperation in the side meeting of the Maranatha Waijoi-Jikomoi congregation is viewed from the pragmatics of conversational implicature that 1) the maxim of quantity of the principle of cooperation at the side meeting of the Marantha congregation of the 24 utterances found contained the maxim of quantity as many as 6 utterances which is considered cooperative; 2) the maxim of quality in the principle of cooperation in the Maranatha congregation's sidi-sidi meeting from 24 utterances containing the maxim of cooperative quality, 10 utterances; and 3) the maxim of relevance in the principle of cooperation in the Maranatha congregation's sidi-sidi meeting. Of the 24 utterances found that contained the maxim of relevance, 8 utterances were considered cooperative. Abstrak Penelitian ini bermaksud mengetahui penerapan prinsip kerja sama dalam rapat Sidi-Sidi Jemaat Maranatha Waijoi-Jikomoi. Penelitian ini dilakukan di jemaat Maranatha desa Waijoi. Teknik pengumpulan data penelitian ini yaitu observasi, dan dokumentasi dalam pendekatan Kualitatif. Dalam mengenalisis data penelitian, peneliti menggunakan reduksi data, penyajianan data dan menarik kesimpulan. Hasil yang ditemukan dalam penelitian ini bahwa prinsip kerja sama dalam rapat sidi-sidi Jemaat Maranatha Waijoi-Jikomoi ditinjau dari pragmatik implikatur percakapan bahwa 1) maksim kuantitas prinsip kerjasama pada rapat sidi-sidi jemaat Marantha dari 24 tuturan yang ditemukan mengandung maksim kuantitas sebanyak 6 tuturan yang dianggap kooperatif; 2) maksim kualitas dalam prinsip kerjasama dalam rapat sidi-sidi jemaat Maranatha dari 24 tuturan yang mengandung maksim kualitas yang kooperatif sebanyak 10 tuturan; dan 3) maksim relevansi dalam prinsip kerjasama dalam rapat sidi-sidi jemaat Maranatha dari 24 tuturan yang ditemukan yang mengandung maksim relevansi sebanyak 8 tuturan yang dianggap kooperatif.